Integrated morphological and molecular characterization of the fish parasitic nematode Rhabdochona (Rhabdochona) gendrei Campana-Rouget, 1961 infecting Labeobarbus altianalis (Boulenger, 1900) in Kenya - Rindoria, Nehemiah M.; Morara, George N.; Smit, Willem J.; Truter, Marliese; Smit, Nico J.; Luus-Powell, Wilmien J. (Elsevier, 2023)
During a parasitological survey carried out between May and August 2022 in the River Nyando, Lake Victoria Basin, a single species of Rhabdochona Railliet, 1916 (Nematoda: Rhabdochonidae) was recorded from the intestine of the Rippon barbel, Labeobarbus altianalis (Boulenger, 1900) (Cyprinidae). Based on light microscopy (LM), scanning electron microscopy (SEM) and DNA analyses the parasite was identified as Rhabdochona (Rhabdochona) gendrei Campana-Rouget, 1961. Light microscopy, SEM and DNA studies on this rhabdochonid resulted in a detailed redescription of the adult male and female. The following additional taxonomic features are described in the male: 14 anterior prostomal teeth; 12 pairs of preanal papillae: 11 subventral and one lateral; six pairs of postanal papillae: five subventral and one lateral, with the latter pair at the level of first subventral pairs when counted from the cloacal aperture. For the female: 14 anterior prostomal teeth and the size and absence of superficial structures on fully mature (larvated) eggs dissected out of the nematode body. Specimens of R. gendrei were genetically distinct in the 28S rRNA and cytochrome c oxidase subunit 1 (cox1) mitochondrial gene regions from known species of Rhabdochona. This is the first study that provides genetic data for a species of Rhabdochona from Africa, the first SEM of R. gendrei, and the first report of this parasite from Kenya. The molecular and SEM data reported herein provide a useful point of reference for future studies on Rhadochona in Africa.
Journal article published in the International Journal for Parasitology: Parasites and Wildlife 21 (2023) 201-209
Keywords: Cyprinidae; Freshwater fish parasite; Helminths; Lake Victoria Basin; Rippon barbel; River Nyando; Rhabdochona; Nematodes; Parasitology -- Research; Cyprinidae